Additive partitioning of spider diversity in a fragmented tropical dry forest (Valle del Cauca, Colombia) (2010)
Abstract Understanding the variation of diversity patterns requires analysis at multiple spatial scales. In this study we estimated the diversity components (alpha, beta and gamma) of the spider community at El Vínculo Natural Regional Park, using the additive partitioning of diversity (species richness, Shannon's diversity index and Simpson's index) for the first time on this taxon in Colombia. We collected the specimens following a nested sampling design that consisted of two spatial scales. At the local scale, we quantified additive diversity components in 238 sampling units, and at the regional scale in five vegetation types. Total observed regional diversity (γ) was partitioned into its additive components: within sampling units (α1), among sampling units (βl) and among vegetation types (β2). We used the same approach to compare common and infrequent spider species and to compare sampling methods. A total of 1565 adult spiders and 72 identifiable juveniles, including 193 morphospecies from 36 familie.